Os processos cognitivos desenvolvidos no ensino de didática no curso de licenciatura em matemática - Figueiredo, Angela Maria Rodrigues de (2012)
This article results of the study accomplished in the Center of Superior Studies of Parintins / UEA and he/she had as theme "The cognitive processes in the didacticism teaching in the degree course in mathematics", the motivation for his/her development was due the little emphasis given to the pedagogic formation of the exits of those courses, being translated in a posture that legitimates the mathematics as isolated of the real and little susceptible context to the I dialogue with the school reality. In an approach process and appropriation of the knowledge to know as the teachers in formation they organize their cognitive processes to give meaning to the pedagogic work, it turns the didacticism, it disciplines integradora of the action teoria/prática and that he/she has fundamental importance in the teacher's professional formation, be of mathematics or other knowledge area. For the recital of our analyses we dialogued with Sternberg (2008), Bransford (2007), Candau (1984); Pimenta (2000); Borges and Ghedin (2010); Astolfi and Develay (1990) and Libâneo (2004) among others.